*June 15, 2018 - Play around with logical operations and their mathematical representations.*

A: 0.00

B: 0.00

= $1 - A$

= 1 - 0.00

= 1.00

A: 0.00

B: 0.00

= $A * B$

=0.00 *0.00

=0.00

A: 0.00

B: 0.00

= $1 - (A * B)$

=1 - (0.00 *0.00)

=1.00

A: 0.00

B: 0.00

= $A + B - A * B$

= 0.00 + 0.00 - 0.00 *0.00

= 0.00

A: 0.00

B: 0.00

= $1 - (A + B - A * B)$

= 1 - (0.00 + 0.00 - 0.00 *0.00)

= 1.00

A: 0.00

B: 0.00

= $A + B - A * B - A * B$

= 0.00 + 0.00 - 0.00 *0.00 - 0.00 *0.00

= 0.00

A: 0.00

B: 0.00

= $1 - (A + B - A * B - A * B)$

= 1 - (0.00 + 0.00 - 0.00 *0.00 - 0.00 *0.00)

= 1.00